The oral fungal mycobiome: characteristics and relation to periodontitis in a pilot study - Peters, Brandilyn A.; Wu, Jing; Hayes, Richard B.; Ahn, Jiyoung (BMC microbiology, 2017)
The oral fungal microbiome (mycobiome) is not well characterized, particularly in relation to oral diseases such as periodontal disease. We aimed to describe and compare the oral mycobiome of subjects with and without periodontal disease. We characterized the oral mycobiome in 30 adult subjects (15 with periodontal disease, 15 with good oral health) by sequencing the taxonomically informative pan-fungal internal transcribed spacer (ITS) gene in DNA extracted from oral wash samples. We observed at least 81 genera and 154 fungal species across all samples. Candida and Aspergillus were the most frequently observed genera (isolated from 100% of participants), followed by Penicillium (97%), Schizophyllum (93%), Rhodotorula (90%), and Gibberella (83%). Candida and Aspergillus were also the most highly abundant genera in the samples (median relative abundance = 21% and 44%, respectively). Aspergillus niger was the most highly abundant species in the samples (median relative abundance = 44%). We did not observe significant differences in overall oral mycobiome diversity or composition between participants with periodontal disease and participants with good oral health, nor did we observe significant differences in phylum through species level taxon relative abundance or carriage between the two groups. Genus Candida, previously associated with periodontal disease in culture-based studies, had higher median relative abundance in participants with periodontal disease (33.2%) compared to participants with oral health (2.2%), though the difference was not significant (p = 0.52). Additionally, within the periodontal disease group, median relative abundance of Candida increased with increasing number of permanent teeth lost (1-2 teeth lost: 3.2%; 3-4 teeth lost: 16.6%; ≥5 teeth lost: 73.9%; p = 0.11), though sample size was small for this analysis. In this first study comprehensively characterizing the oral mycobiome of adults with periodontal disease or good oral health, we observed trends of higher Candida abundance in participants with periodontal disease, and participants with greater tooth loss. Small sample size may have limited the power to detect significant associations. Larger studies including subgingival samples may further establish the core oral mycobiome in health, and relate it to periodontal disease.